P08.05 Cognitive impairment in patients with newly-diagnosed high-grade gliomas. (6th September 2019) - Ribeiro, M; Durand, T; Jacob, J; Psimaras, D; Noel, G; Feuvret, L; Hoang-Xuan, K; Roussel, M; Godefroy, O; Bernier, M; Ricard, D
Abstract: BACKGROUND: Cognitive dysfunction is frequent in patients with primary brain tumor, impairing attention, memory and executive function. It compromises functional independence, decision making capacity and psycho-social well-being. Cognitive functioning is highly correlated to disease progression and quality of survival, thus cognitive follow-up is essential in the management of the disease. Cognitive screening tools are often used, since a comprehensive battery may be time consuming and challenging for patients. The objective of this study was to identify a pattern of cognitive dysfunction in patients with newly-diagnosed high-grade gliomas and evaluate the sensitivity and specificity of the MoCA (Montreal Cognitive Assessment ) as a cognitive screening tool in the clinical practice. MATERIAL AND METHODS: We compared performances in tests of memory, action speed, visuospatial ability and executive function of 156 patients with newly-diagnosed WHO Grade III and IV gliomas, after surgery and prior to radiochemotherapy, to those of a group of healthy controls (n=1003). Relatives assessed behavior through a questionnaire of behavioral dysexecutive syndrome. A stepwise logistic regression was performed to select cognitive domains better discriminating patients from healthy controls and we tested the sensitivity and specificity of the MOCA using ROC curve analysis. RESULTS: The stepwise logistic regression analysis identified the 3 following factors better discriminating patients from controls: TMT-B completion time (OR: 0.673; 95% CI: 0.511–0.886; p=0.0005), a verbal memory index (OR:0.507; 95% CI: 0.358–0.718; p=0.0001) and a behavioral dysexecutive score (OR:0.616; 95% CI: 0.468–0.812, p=0.001). Prevalence of cognitive-behavioral impairment was of 35.94%; 95% CI: 28.3 - 43.5. The ROC curve analysis for the assessment of the MoCA sensitivity and specificity in detecting impairment yielded 0.795 (95%CI: 0.714–0.875) for the MoCA raw score, and 0.804 (95%CI: 0.727 - 0.881) for the adjusted z score. The optimal discrimination was obtained for a raw score ≤ 25 (sensitivity of 0.526; specificity of 0.832). For the adjusted score, optimal discrimination value was observed with a -0.603 z score (sensitivity of 0.716; specificity of 0.768). CONCLUSION: Cognitive impairment and behavioral dysexecutive syndrome is frequent in patients with newly-diagnosed high-grade glioma. The MoCA lacks sensitivity in screening cognitive impairment to discriminate patients from healthy controls in this setting, and a comprehensive neuropsychological assessment is still recommended.